2003
DOI: 10.1002/jmv.10559
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B viremia is associated with increased risk of hepatocellular carcinoma in chronic carriers

Abstract: The role of quantitative viral load in development of hepatocellular carcinoma (HCC) among chronic hepatitis B virus (HBV) carriers was evaluated using real-time PCR (TaqMan PCR), a highly sensitive method for quantitative detection of HBV DNA. Serum samples collected at study entry from HCC cases and matched controls were chosen separately from ongoing prospective cohort studies in Senegal, West Africa, and Haimen City, China. For 14 HCC cases and 28 controls from Senegal, the relative risk (RR, 95% CI) of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 13 publications
4
68
0
1
Order By: Relevance
“…This higher replication efficiency of HBV in males provides an explanation as to why there are more male HBV carriers than female HBV carriers. It also provides an explanation as to the gender discrepancy in the incidence of HCC, as HBV viral load has been shown to be a major risk factor for HCC (2,4,11).…”
Section: Discussionmentioning
confidence: 99%
“…This higher replication efficiency of HBV in males provides an explanation as to why there are more male HBV carriers than female HBV carriers. It also provides an explanation as to the gender discrepancy in the incidence of HCC, as HBV viral load has been shown to be a major risk factor for HCC (2,4,11).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that serum level of HBV DNA may be a risk factor for HCC [13][14][15][16] . Tang et al [17] have previously reported that adult HBV carriers who maintain high-titer serum HBV DNA are at higher risk for development of HCC. In Taiwan, a 12-year follow-up study of 4841 men who were Hepatitis B surface antigen (HBsAg) positive has demonstrated that the risk of HCC is 2.7-10.7-fold higher in patients with baseline HBV DNA levels of 4.0 log10 copies/mL to ≥ 6.0 log10 copies/mL [18] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the virus levels decrease and hepatitis abates. Some patients, however, remain positive for HBeAg, and in those patients the hepatitis virus persists at high levels, resulting in the progression to hepatic cirrhosis and the onset of hepatocellular carcinoma (HCC) in a high percentage of such patients [3,4,5]. The number of HBV carriers is decreasing in Japan and some other countries as a result of the prevention of mother-child transmission through the use of HBV vaccines and/or high-potency antibody to hepatitis B surface antigen (HBsAb) human immunoglobulin (HBIG) [6].…”
Section: Introductionmentioning
confidence: 99%